Abiotic and Biotic Factors Affecting Loblolly Pine Health in the Southeastern United States. Issue 2 (26th August 2019) - Coyle, David R; Barnes, Brittany F; Klepzig, Kier D; Koch, Frank H; Morris, Lawrence A; Nowak, John T; Otrosina, William J; Smith, William D; Gandhi, Kamal J K
Abstract: Southern pine forests are important fiber and wood sources, and critical to local, regional, and national economies in the United States. Recently, certain areas of southern pine forests, especially those dominated by loblolly pine ( Pinus taeda ), have been reported to exhibit abnormally high levels of tree dieback and mortality. However, causal agents either have not been well defined or are controversial in their impacts on tree health. We assessed various abiotic (e.g., slope, aspect, soil characteristics) and biotic (e.g., tree species, stand characteristics, presence of root fungi) factors in 37 healthy (asymptomatic) and unhealthy (symptomatic) sites to elucidate specific factors affecting loblolly pine health in Alabama and Georgia. Soil nutrient content did not differ statistically between healthy and unhealthy sites, but manganese contents were slightly greater, and nitrogen and carbon contents were slightly lower in healthy sites. Unhealthy sites did have a higher silt content than did healthy sites. Pine stems and basal area were greater on unhealthy than on healthy sites, whereas opposite trends were observed for the incidence of stem cankers and mechanical damage. An increased incidence of the root fungal pathogen Heterobasidion irregulare, the causal agent of Heterobasidion root disease, was found on unhealthy sites, but incidence of Leptographium spp. did not differ between the two site types. Thus, soil attributes, stand structure, and management history seem to be the most critical factors affecting loblolly pine health, at least at the local level. Further, some of these factors may be improved through appropriate silvicultural techniques, emphasizing the importance of silviculture in maintaining pine health throughout the southern region.